Maternal toxoplasmosis and the risk of childhood autism: serological and molecular small-scale studies - Jamila S. Al Malki; Nahed Ahmed Hussien; Fuad Al Malki (BMC, 2021)
Abstract Background Toxoplasmosis resulting from infection with the Toxoplasma parasite has become an endemic disease worldwide. Recently, a few studies have reported a high prevalence of Toxoplasmosis infections among Saudi Arabian women. This disease could become life threatening for pregnant women and for immunodeficient people. There is evidence that infections during pregnancy, especially in the early stages, are associated with neurodevelopmental disorders. Autism disorder represents one of the most common neurodevelopmental disorders worldwide; it is associated with delayed language development, weak communication interaction, and repetitive behavior. The relationship between prenatal toxoplasmosis and autism in childhood remains unclear. The present study aims to report a link between maternal toxoplasmosis and autistic offspring among Saudi Arabian women. Method Blood samples (36 maternal, 36 from their non-autistic children, and 36 from their autistic children) were collected for serological and molecular evaluation. Results A toxoplasmosis infection was reported for 33.34% of participants using an ELISA assay (5.56% IgG+/IgM+, 11.11% IgG−/IgM+, and 16.67% IgG+/IgM-); however, a nested PCR assay targeting B1 toxoplasmosis specific genes recorded positive tests for 80.56% of the samples. In addition, the present study detected several points of mutation of mtDNA including NADH dehydrogenase (ND1, ND4) and Cyt B genes and the nDNA pyruvate kinase (PK) gene for autistic children infected with toxoplasmosis. Conclusion Considering previous assumptions, we suggest that a maternal toxoplasmosis infection could have a role in the development of childhood autism linked to mtDNA and nDNA impairment.